Evaluation of the clinical effectiveness of modified sacrospinous ligament fixation via the anterior vaginal wall path for pelvic organ prolapse: A feasibility report based on 50 patients - Lyu, Yuanyuan; Ding, Huafeng; Zhang, Ying; Shi, Suhua; Ding, Jin; Zhu, Chengcheng; Guan, Xiaoming; Ni, Guantai; Luo, Yonghong (Frontiers in Surgery, 2022)
Objective: To describe the surgical techniques and short-term outcomes for 50 cases of modified sacrospinous ligament fixation via the anterior vaginal wall path for pelvic organ prolapse Methods：100 patients with pelvic organ prolapse (stage Ⅲ or stage Ⅳ based on POP-Q staging) from January 2018 to January 2020 were retrospectively analyzed. Among them, 50 patients received modified sacrospinous ligament fixation via the anterior vaginal wall path for pelvic organ prolapse (mSSLF group), while the other 50 patients received pelvic reconstruction using T4 mesh (T4 group). Operative time, blood loss, postoperative POP-Q score, length of the hospital stay, complications, and postoperative pain were compared between the two groups. Results：The duration of the operation in mSSLF group was (50± 15.2 minutes), which was shorter than that of the T4 group (60±14.8 minutes) (p=0.04). No intraoperative complications were reported from the mSSLF group, whereas one vascular injury occurred in the T4 group. In both groups, postoperative pain was significantly lower in the mSSLF group than in the SSLF group (p < 0.001). The exposed mesh rate was lower than T4 group. However, postoperative anterior pelvic prolapse was not significantly different between the two groups. Conclusions：The rates of intraoperative complications, postoperative pain and mesh erosion were significantly lower than those of the T4 group, but there was no significant difference in the efficacy and safety of the treatment of pelvic organ prolapse. So mSSLF may be a feasible technique to manage severe prolapse, with promising short-term efficacy and safety.